Odpowiedzi

  • Użytkownik Zadane
2009-11-23T11:21:52+01:00
A)
x=0
x=-4
x=2
b)
x2(x+3)-4(x+3)=0
(x2-4)(x+3)=0
x=-2
x=2
x=-3
2009-11-23T12:56:57+01:00
A). x(x+4)²(x-2)=0
x(x²+8x+16)(x-2)=0
(x³+8x²+16x)(x-2)=0
x⁴+8x³+16x²-2x³-16x²-32x=0
x⁴+6x³=0
x3(x+6)=0
x=0
x=-6

b).x³+3x²-4x-12=0
x²(x+3)-4(x+3)=0
(x²-4)(x+3)=0
x²=4/√
x=2
x=-2
x=-3
2009-11-23T13:29:48+01:00
A).
x(x²+8x+16)(x-2)=0
(x³+8x²+16x)(x-2)=0
x⁴+8x³+16x²-2x³-16x²-32x=0
x⁴+6x³=0
x3(x+6)=0
x=0
x=-6

b).
x³+3x²-4x-12=0
x²(x+3)-4(x+3)=0
(x²-4)(x+3)=0
x²=4/√
x=2
x=-2
x=-3